The evolutionary ecology of technological innovations. Issue 4 (8th February 2013) - Solée, Ricard V.; Valverde, Sergi; Casals, Marti Rosas; Kauffman, Stuart A.; Farmer, Doyne; Eldredge, Niles
Abstract Technological evolution has been compared to biological evolution by many authors over the last two centuries. As a parallel experiment of innovation involving economic, historical, and social components, artifacts define a universe of evolving properties that displays episodes of diversification and extinction. Here, we critically review previous work comparing the two types of evolution. Like biological evolution, technological evolution is driven by descent with variation and selection, and includes tinkering, convergence, and contingency. At the same time, there are essential differences that make the two types of evolution quite distinct. Major distinctions are illustrated by current specific examples, including the evolution of cornets and the historical dynamics of information technologies. Due to their fast and rich development, the later provide a unique opportunity to study technological evolution at all scales with unprecedented resolution. Despite the presence of patterns suggesting convergent trends between man‐made systems end biological ones, they provide examples of planned design that have no equivalent with natural evolution.